2014
DOI: 10.1111/ap.12057
|View full text |Cite
|
Sign up to set email alerts
|

Child Adjustment and Parent Efficacy Scale: Development and Initial Validation of a Parent Report Measure

Abstract: This study examined the psychometric characteristics of the Child Adjustment and Parent Efficacy Scale (CAPES). The CAPES was designed as a brief outcome measure in the evaluation of both public health and individual or group parenting interventions. The scale consists of a 30-item intensity scale with two subscales measuring children's behaviour problems and emotional maladjustment and a 20-item self-efficacy scale that measures parent's self-efficacy in managing specific child problem behaviours. A sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 58 publications
4
97
1
2
Order By: Relevance
“…Convergent validity. Three standard approaches were applied to assess convergent validity of the factor structures: (i) we evaluated the statistical significance and magnitude of factor loadings; (ii) checked that the estimate of the Average Variance Extracted (AVE) which is shared between the construct and its measures is above .50; and (iii) tested that estimates of Composite Reliability (CR) were above .70 (Fornell & Larcker, 1981;Morawska et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Convergent validity. Three standard approaches were applied to assess convergent validity of the factor structures: (i) we evaluated the statistical significance and magnitude of factor loadings; (ii) checked that the estimate of the Average Variance Extracted (AVE) which is shared between the construct and its measures is above .50; and (iii) tested that estimates of Composite Reliability (CR) were above .70 (Fornell & Larcker, 1981;Morawska et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Child adjustment and parent efficacy scale (CAPES; Morawska et al, 2014). The CAPES is a 27-item measure that assesses child emotional and behavioural problems and parental self-efficacy.…”
Section: Methodsmentioning
confidence: 99%
“…The scale consists of a 30-item intensity scale with two subscales measuring children's behaviour problems and emotional maladjustment, and a 20-item self-efficacy scale measuring parent's self-efficacy in managing specific child problem behaviours. The initial validation study found the internal consistency for the CAPES to be excellent for Intensity (α = .90), Behaviour (α = .90) and SelfEfficacy (α = .96), and adequate for Emotional Maladjustment (α = .74) (Morawska, Sanders, et al, 2014). Regarding construct validity, CAPES intensity showed reasonable convergent validity as measured by AVE estimates (average variance extracted), CR estimates (composite reliability), and examination of factor loadings.…”
Section: Child Behaviourmentioning
confidence: 94%
“…The Child Adjustment and Parent Efficacy Scale (CAPES; Morawska, Sanders, Haslam, Filus, & Fletcher, 2014) assesses the level of child emotional and behavioural difficulties. The scale consists of a 30-item intensity scale with two subscales measuring children's behaviour problems and emotional maladjustment, and a 20-item self-efficacy scale measuring parent's self-efficacy in managing specific child problem behaviours.…”
Section: Child Behaviourmentioning
confidence: 99%
See 1 more Smart Citation